Perencanaan Sistem Transmisi Dan Distribusi Air Bersih Di Desa Fatumonas - Zofar Agluis Banunaek (Jurnal Ecocentrism, 2023)
Fatumonas Village is located in Amfoang Tengah Sub-district, Kupang Regency, East Nusa Tenggara Province, which has an area of 32.76 Km² and has a population of 2119 people in 2022. There are 7 spring locations, but there are several spring locations that are not located near settlements, making it difficult for people to reach and obtain clean water. The need for clean water is calculated based on population projections analyzed using the geometric method. Spring planning in the form of transmission and distribution pipeline maps planned 2 springs namely Haukauna Spring, Oelpel Spring is done by pump and gravity.